Detection of a new crescent moon using the maximally stable extremal regions (MSER) technique - Zulkeflee, A. N. (Elsevier, 2022)
Visibility of a new crescent moon is crucial for Muslims when declaring the beginning of the Islamic calendar. For many years, astronomers had observed the visibility of the new crescent moon using various techniques, such as the naked eye and optical instruments. In line with technological developments, astronomers have changed their observation technique to using astronomical imaging with the aid of a digital camera attached to a telescope. This helps to capture and save the images of the new crescent moon. However, the new crescent moon image has presented difficulties to astronomers as it visibility in the image is difficult to detect due to a low contrast with the sky. Hence, the captured image could not be presented as evidence of its visibility. This study proposes the use of Contrast Limited Adaptive Histogram Equalization (CLAHE) for contrast enhancement. Then, the bilateral filter for image denoising was applied and lastly, the Maximally Stable Extremal Regions (MSER) detector was used to detect the new crescent moon region in the image. The result shows that this proposed method has acceptable practical results. The new crescent moon images can be enhanced successfully using CLAHE and the bilateral filter technique even when the new crescent moon is not visible to the naked eye. The new crescent moon region can be well detected with the MSER detector although MSER does not perform well on the blurry region of new crescent moon corner. This technique can help astronomers detect the new crescent moon's visibility for declaring the beginning month of the Islamic calendar.(c) 2022 Elsevier B.V. All rights reserved.